THE EFFECT OF EDUCATION LEVEL, INVESTMENT, AND MINIMUM WAGE ON THE ACTIVE LABOR FORCE OF KERINCI REGENCY - Syofya, Heppy; Judijanto, Loso; Widiyarini, Widiyarini; Samiun, Muhammad Zais M; Hananto, Praditya Mer (Journal of Management Small and Medium Enterprises (SMEs), 2024)
Indonesia has a rapid population growth but it is not matched by employment opportunities for the labour force. Increased productivity will run well if accompanied by the appropriate Regional Minimum Wage (UMR). The Regional Minimum Wage is the minimum standard applied by businesses in paying wages to employees, employees, or labourers who work in their business. The Regional Minimum Wage always increases every year, which is applied to increase the workforce's desire to be able to work. This research will examine the effect of education level, investment, and minimum wage on active labour. The research method used in this study is quantitative research. The type of data source uses secondary data collected through the Central Bureau of Statistics report. The data analysis technique uses path analysis which is processed through the SPSS version 23 application with a total of 140 respondents. This research was conducted in Kerinci Regency with research time from August 2023 - October 2023. The results of this study found that there is an effect of education level, investment, and minimum wage on the active labour force in Kerinci Regency. Keywords: Active Labour Force; Education Level; Investment; Minimum Wage